“Woli w Polszcze leda schaby / Niż tu ostrygi i żaby / Woli zraz pieczeni spory / Niźli kaulafiory”. Italian cuisine in the eyes of Polish peregrinates - Szadkowska-Mańkowska, Olga (Perspektywa stołu, 2023)
The cultural relations between Poland and Italy over the centuries have been an important element in historical and literary discussions. There is no doubt that Italianism – understood more as a way of perceiving Italy, resulting from the role played by Italy in Western culture, than as a doctrine about Italy – meant a completely new concept of sightseeing. Interestingly, it was not only the architecture, painting, sculpture or the exceptionally favourable Italian climate that evoked emotions in Polish peregrinates. Italian cuisine also remained in the circle of their interest. The love for Italian cuisine is not a homogenous subject – solid meat and dignified Polish drinks were often contrasted with Italian “exquisiteness”. The traditionalists of Polish society, stuck in the cult of the old custom and not venturing beyond Polish borders, have certainly contributed to the poor reputation of Italian fashion, including Italian cuisine. And although the majority of voices on the shadows and glories of Italian food belong to men, as they travelled more often, an interesting source for analysing everyday life on the road are the memories of women-peregrinates. Teofilia Morawska, Waleria Tarnowska or Katarzyna Sosnowska Platerowa are examples of Polish female travellers of the turn of the 18th and 19th centuries, who enriched this topic with their reflections. Irrespective of the purpose and reason for a woman’s journey, each in her own way broadened her horizons and brought about an experience invaluable in human life. They described what they encountered in a balanced way, reflecting calmly because they felt a complete connection with Western Europe and its cultural life. They often included the reality of the country they knew – also from the “table” side. Did we really “fall in love with Italian cuisine only in the 20th century”? In my article, I would like to take up the issue of Polish attitude towards Italian cuisine in women’s travel memoirs of the early 19th century.